Penggunaan Radiasi di Bidang Kedokteran - Soeroyo, Soeroyo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1980)
The application of radiation in medicine is both for diagnostic as well as therapeutic purposes, and is more widespread than ever before.The role of X- and Y-rays in cancer therapy is becoming more frequent, because: 1, there are more people in the old-age group,2. progress as continually made in radiations techniques.Since ionisation radiation is destructive to living cells, its application must be done with care and under the supervision of an expert radiologist.Key Wards: radiology - diagnostic and therapeutic radiation - fluoroscopy - radiography - cancer treatment